Improving chances? A design strategy to improve health and wellbeing for marginalised people - Smith, Dianne; Karol, E. (Australasian Medical Journal Pty Ltd, 2017)
© 2017, Australasian Medical Journal Pty Ltd. All rights reserved. Background There is a call for architects and designers to rethink what is meant by design for health. Therapeutic design in everyday settings is a growing area of concern Aims The authors aim to provide alternative ways of approaching the design of facilities or places that integrate the end-user as a collaborator in the evolution of design ideas in order to create places, which will support their wellbeing. Methods The research integrated a theoretical Model with creative practice as research before gaining insights from the end-users and provider of a case study, a day facility for people who are homeless. Results The results are twofold. Firstly a Socio-Ecological Design Model (SEDM) and secondly, insights into a designing supportive environments for people who are homeless as an example of a marginalised group.Conclusion It is possible to undertake a collaborative and informed process, which can act as a catalyst for positive change and challenge the current common processes to date.